P148 JAK-inhibition by baricitinib and tofacitinib ameliorates pathological bone loss. (March 2019) - Adam, S; Simon, N; Steffen, U; Andes, F; Müller, D; Culemann, S; Andreev, D; Hahn, M; Scholtysek, C; Schett, G; Krönke, G; Frey, S; et al.
Abstract : Career situation of first and presenting author: Student for a master or a PhD. Introduction: Many cytokines relevant to rheumatoid arthritis (RA) rely on the janus kinase – signal transducer and activator of transcription (JAK-STAT) signaling pathway. The JAK-inhibitors tofacitinib and baricitinib, targeting JAK3/JAK1 and JAK1/JAK2 respectively, have been approved for treatment of RA 1 . While currently available therapies reduce inflammation, erosive damage in involved joints is still irreversible. However, preliminary data suggests an influence of JAK inhibition on local bone healing. Objectives: To study the role of JAK-inhibition in osteoblast and osteoclast-mediated bone homeostasis and its capacity to alleviate structural bone damage in vivo . Methods: For steady state analysis C57BL/6 (WT) mice received tofacitinib QD by oral gavage for 6 weeks. WT mice of the ovariectomy-induced osteoporosis model (OVX) obtained tofacitinib BID by oral gavage for 6 weeks. For the serum-induced arthritis model (SIA) WT mice received tofacitinib or baricitinib BID by oral gavage for 14 days. Readout covered serum cytokine levels (ELISA), µCT and mRNA analysis of bone (qPCR) and clinical scoring. Murine osteoclasts (OC) were assessed for differentiation (TRAP staining) and resorption (Von Kossa staining). Murine mesenchymal stem cell (MSC)-derived and primary osteoblasts (OB) were analyzed for differentiation (qPCR) and function (Alizarin red staining). Results: In unchallenged WT mice, treatment with tofacitinib increased trabecular bone density in tibia and reduced RANKL/OPG ratio in serum. These results, along with elevated trabeculae numbers, also applied to spinal bone in tofacitinib-treated OVX mice. In SIA, baricitinib and tofacitinib ameliorated disease manifestation and inhibited trabecular/cortical bone loss. In vitro JAK-inhibition exhibited no effect on differentiation and function of OCs. However, it enhanced OCN expression in MSC-derived OBs at day 1 after osteoblastic induction and led to decreased Igf1 and increased Dkk1 expression at day 7. Accordingly, primary OBs showed reduced RANKL expression during JAK-inhibition. Moreover, both MSC- and primary OBs responded to JAK-inhibition with increased mineralization. Conclusions: Our findings indicate that JAK-inhibition by tofacitinib and baricitinib increases bone formation in vivo, in both steady-state and pathological conditions, presumably as a result of increased mineralization capacity by osteoblasts. Reference: Baker KF, Isaacs JD. ARD 2018. Acknowledgements: Work funded by Pfizer and Eli Lilly. Disclosure of Interest: S. Adam Grant/research support from: Pfizer, Eli Lilly, N. Simon: None declared, U. Steffen: None declared, F. Andes: None declared, D. Müller: None declared, S. Culemann: None declared, D. Andreev: None declared, M. Hahn: None declared, C. Scholtysek: None declared, G. Schett: None declared, G. Krönke: None declared, S. Frey: None declared, A. Hueber: None declared.